2001
DOI: 10.1111/1468-2389.00160
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Performance at the Beginning of the New Millennium: What Do We Know and Where Do We Go Next?

Abstract: As we begin the new millennium, it is an appropriate time to examine what we have learned about personality-performance relationships over the past century and to embark on new directions for research. In this study we quantitatively summarize the results of 15 prior meta-analytic studies that have investigated the relationship between the Five Factor Model (FFM) personality traits and job performance. Results support the previous findings that conscientiousness is a valid predictor across performance measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

112
1,731
25
66

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,880 publications
(1,934 citation statements)
references
References 53 publications
112
1,731
25
66
Order By: Relevance
“…However, this a relatively untouched area in medicine selection, despite the pressing need for medical professionals to ''do more with less'', and the changing nature of many medical roles to require entrepreneurialism in the future (Gregory 2009). Patterson and Zibarras (2016) note that conscientiousness and innovation have been found to correlate negatively, which raises a challenging dilemma since previous research has consistently shown a positive association between conscientiousness and various indices of education and training success and job performance (McLachlan and Macnaughton 2009;Woods et al 2016;Barrick et al 2001). This study explores the use of a trait-based measure of creativity and innovation potential and evaluates its efficacy for use in selection for medical education; finding that different aspects of innovation are associated with different sub-facets of conscientiousness, and that motivation to change is the key significant predictor of creative problem solving, over and above personality traits.…”
Section: How Can We Best Select For Important Personal Attributes Andmentioning
confidence: 99%
“…However, this a relatively untouched area in medicine selection, despite the pressing need for medical professionals to ''do more with less'', and the changing nature of many medical roles to require entrepreneurialism in the future (Gregory 2009). Patterson and Zibarras (2016) note that conscientiousness and innovation have been found to correlate negatively, which raises a challenging dilemma since previous research has consistently shown a positive association between conscientiousness and various indices of education and training success and job performance (McLachlan and Macnaughton 2009;Woods et al 2016;Barrick et al 2001). This study explores the use of a trait-based measure of creativity and innovation potential and evaluates its efficacy for use in selection for medical education; finding that different aspects of innovation are associated with different sub-facets of conscientiousness, and that motivation to change is the key significant predictor of creative problem solving, over and above personality traits.…”
Section: How Can We Best Select For Important Personal Attributes Andmentioning
confidence: 99%
“…Consistent with this perspective, Hogan (2003) categorized self-report of personality as an indicator of identity and observer-report of personality as an indicator of reputation. According to Hogan, Hogan, and Roberts (1996), reputation, which is ratings by knowledgeable others, is the best way to conceptualize personality (c.f., Barrick et al, 2001). …”
Section: Personality Task Performance and Helpingmentioning
confidence: 99%
“…There is a growing body of research from applied psychology showing that personality and other noncognitive variables are predictive of performance across a wide range of occupations and are generally uncorrelated with and add incremental validity over and above cognitive ability, and that predictive validities differ by job content and performance requirements (Barrick & Mount, 1991;Barrick, Mount, & Judge, 2001;Hough & Furnham, 2003;McHenry, Toquam, Hanson, & Ashworth, 1990;Mount & Barrick, 1995;Mount, Barrick, & Stewart, 1998;Schmidt & Hunter, 1998). More specific to the Army, research from Project A demonstrated that predictor composites reflecting different mixes of cognitive aptitudes, personality traits, interests, and background characteristics more strongly differentiated and predicted performance, including technical proficiency, across jobs than predictor composites based on aptitude alone (Wise, McHenry, & Campbell, 1990).…”
Section: Suggestions For Future Researchmentioning
confidence: 99%